PP51 Implementation of a predictive risk tool in primary care: examining understanding and engagement among practitioners. (2nd September 2014) - Kingston, MR; Porter, AM; Evans, BA; Hutchings, HA; Snooks, HA
Abstract : Background: Through new contractual arrangements, general practitioners (GPs) are encouraged to use computer-based predictive risk tools to identify patients who might benefit from community interventions to avoid inappropriate emergency admissions. However, little is known about how receptive GPs and their colleagues are likely to be to adopting such tools. As part of the PRISMATIC trial of the Prism risk tool in Wales, we used qualitative work in primary care to explore practitioners' expectations prior to using Prism, in order to better understand the process of implementation of this new technology. Methods: All practices (n = 32) taking part in the trial were invited to participate in the qualitative fieldwork. Before practices received Prism, we held 4 focus groups of GPs and other practice staff, and interviewed those who were unable to attend a focus group. We asked about expectations of Prism use and impact, and any concerns. We recorded the groups and interviews. We analysed transcripts thematically, informed by Normalisation Process Theory (NPT), focusing on the processes of coherence (understanding of the innovation) and engagement (wanting to use it). Results: 19 GPs, 9 Practice Managers and 3 Practice Nurses took part in the focus groups, and we interviewed a further 11 GPs. Coherence seemed strong, with respondents generally supporting the principle of identifying at-risk patients, already familiar with risk prediction from using condition specific tools, and willing to trial Prism. They felt it fitted with policy imperatives. They saw Prism as relatively straightforward to install and use. In terms of engagement, Prism appealed to their desire to improve care of patients at risk of emergency admissions. However, respondents felt challenged by limited capacity, within the practice and among community staff, to respond to identified needs. There were anxieties about raising patient expectations, and about implications in terms of performance management. Conclusion: Though respondents were open to trying Prism, it will need to be part of a bigger picture of community based services. The findings will have UK and international relevance at a time of heightened focus on emergency admissions.